Embedded Systems: Design, Analysis and Verification 4th IFIP TC 10 International Embedded Systems Symposium, IESS 2013, Paderborn, Germany, June 17-19, 2013, Proceedings - Schirner, Gunar; Götz, Marcelo; Rettberg, Achim; Zanella, Mauro C.; Rammig, Franz J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 4th IFIP TC 10 International Embedded Systems Symposium, IESS 2013, held in Paderborn, Germany, in June 2013. The 22 full revised papers presented together with 8 short papers were carefully reviewed and selected from 42 submissions. The papers have been organized in the following topical sections: design methodologies; non-functional aspects of embedded systems; verification; performance analysis; real-time systems; embedded system applications; and real-time aspects in distributed systems. The book also includes a special chapter dedicated to BMBF funded ARAMIS project on Automotive, Railway and Avionics Multicore Systems.
Design methodologies -- Non-functional aspects of embedded systems -- Verification -- Performance analysis -- Real-time systems -- Embedded system applications -- Real-time aspects in distributed systems.
Keywords: Special purpose computers; Computer system failures; Software engineering; Computer-aided engineering; Special Purpose and Application-Based Systems; System Performance and Evaluation; Software Engineering; Computer-Aided Engineering (CAD, CAE) and Design